A CASE STUDY OF COMBINED PEER-TEACHER FEEDBACK ON PARAGRAPH WRITING AT A UNIVERSITY IN THAILAND - Loan, Nguyen Thi Thuy (Indonesian Journal of Applied Linguistics, 2017)
Writing in English is challenging for ESL writers, so feedback is crucial in assisting them. Although several studies have been conducted on the effectiveness of peer and teacher-feedback in ESL writing, studies on the combined peer-teacher feedback model tend to be scarce. This study thus reported on the combined feedback model in two paragraph-writing classes of sixty students at a university in Thailand where English is taught as a foreign language, students are reported to be passive in class activities and most writing programs are still taught using the traditional method. Students’ peer comments (both valid and invalid ones), their revisions based on both their peers’ and teacher’s feedback (correct and incorrect revisions) and their grades on each paragraph were recorded, and a five-point Likert scale survey and a focus group interview were conducted. The findings indicated its success in terms of students’ positive attitudes towards this feedback model, the usefulness of peer comments, high percentages of feedback incorporations and the high overall writing scores. This paper is thus expected to shed some light on how Thai university students with their passive style of learning English positively react to this interactive activity and partly reflect how in-service teachers adjust feedback strategies in their actual teaching situations.